Action of andiroba oil (Carapa guianensis) on Rhipicephalus sanguineus (Latreille, 1806) (Acari: Ixodidae) semi-engorged females: Morphophysiological evaluation of reproductive system - Vendramini, Maria Claudia Ramalho [UNESP]; Mathias, Maria Izabel Camargo [UNESP]; Faria, Adriano Uemura de [UNESP]; Furquim, Karim Christina Scopinho [UNESP]; Souza, Leonardo Peres de [UNESP]; Bechara, Gervasio Henrique [UNESP]; Roma, Gislaine Cristina [UNESP] (Wiley-Blackwell, 2012)
Because of the increasing medical-veterinary importance of ticks, the development of alternative control methods, less aggressive to the host and the environment has become the target of several researches. In this sense, the present study analyzed the action of different concentrations (5, 10, and 20%) of andiroba seed oil (Carapa guianensis) on the reproductive system of Rhipicephalus sanguineus females, through histochemical techniques and the quantification of the reproductive efficiency index. The results showed that andiroba oil is a potent natural agent, able to cause several changes in the oocytes of this species, impairing the reproductive success, once this natural product induces great physiological changes in the oocytes in all development stages, such as drastic reduction in proteins, polysaccharides, and lipids in these cells, and these components are essential for the viability of the embryo. In addition, it was observed that this product stimulate the oviposition, mainly at the concentration of 20%. This higher production of eggs represents a defense mechanism developed by the organism in order to ensure the reproductive success of the species, even in the presence of the toxic agent. However, the results obtained suggested that the laid eggs would not be viable, due to the great changes undergone by the oocytes. Thus, the present study showed that the use of this vegetal product would be an alternative way to control the ticks, bringing benefits similar to the ones obtained through the use of synthetic acaricides; however, with less damage to nontarget organisms and the environment as well. Microsc. Res. Tech., 2012. (C) 2012 Wiley Periodicals, Inc.
Keywords: Ticks; Natural product; Germ cells; Cytotoxicity; reproductive efficiency index